Diversitas Makrozoobentos di Kawasan Ekosistem Mangrove Berdasarkan Perbedaan Substrat Desa Pejarakan, Kecamatan Gerokgak, Buleleng - Syury, Ratih Permitha; Dharma, IGB Sila; Faiqoh, Elok (Journal of Marine Research and Technology; Vol 2 No 1 (2019): FEBRUARI 2019DO - 10.24843/JMRT.2019.v02.i01.p01, 2019)
Mangrove ecosystem in Pejarakan Village is an area that is functioned as a region by community group NCF Putri Menjangan, Gerokgak. This makes the diversity of marine life one of the macrozoobentos can breed well. In addition, the presence of mangrove vegetation and various substrates also affect the diversity of macrozoobenthos. The method of this research used a purposive sampling method to determine the location of mangrove sampling assumed by using the different of substrate at each station area of 10 x 10 Meters. After that, in that transect done is taking samples of macrozoobenthos with 1 X 1 meters transect. This substrate difference affects the value of composition gained, on species values obtained for the highest mangrove vegetation present in station 3 in the genus Sonneratia by 62%. While for the highest density and diversity of mangrove is found in station 2 with density value 0,09 ind / m 2 and diversity value equal to 0,937. Others with the highest density and diversity values for macrozoobenthos occurred at station 1 with macrozoobenthos density of 25.50 ind / m 2 , while for macrozoobenthos diversity value of 2.865. Therefore, the diversity category for mangroves belongs to a very diverse diversity category with diversity of macrozoobenthos which belong to various categories of moderate diversity. Therefore, this condition is assumed by the amount of substrate occurring at the 1st station of the clay building, the 2nd station in the form of dusty clay and the 3 clay form stations, can affect the various types that exist in each station. This is because each macrozoobenthos has the ability to each adjust to its habitat.